The impact of tumor microenvironment and treatment schedule on the effectiveness of radiation therapy - Kyprianos Dimou; Yiannis Roussakis; Constantinos Zamboglou; Triantafyllos Stylianopoulos (PLoS ONE, 2025)
External Beam Radiation Therapy (EBRT) is predominantly administered using Conventionally Fractionated Radiotherapy (CFRT), that is 2 Gy per fraction. However, Moderately Hypofractionated Radiotherapy (MHRT) (approx. 2.5–3 Gy per fraction) and Stereotactic Body Radiotherapy (SBRT) (approx. 6–24 Gy per fraction) regimen are currently clinically investigated or even recently included in standard clinical practice. In addition, hyperfractionated radiotherapy (<1.8–2 Gy per fraction) is also clinically investigated or already used in standard clinical practices. The therapeutic effects of each of these radiotherapy schedules might depend on the degree of radioresistance of the tumor but also on properties of the tumor microenvironment, such as tumor perfusion and oxygenation. Here, building on previous work, we developed a mathematical model to investigate optimal radiotherapy treatment protocols in solid tumors. The model incorporates direct effects of radiation on cancer cells and accounts for the impact of tumor perfusion and oxygenation on the efficacy of radiation therapy. The model was able to accurately reproduce both preclinical and clinical data from different radiotherapy treatment schedules. It confirmed that greater tumor perfusion and thus, oxygenation improves treatment effectiveness by increasing the number of cancer cells killed during the treatment period. It further predicted that this effect is more pronounced for radioresistant tumors, meaning that changes in tumor perfusion of more radioresistant tumors have a greater impact on the percentage of surviving cells at the end of the treatment. The mathematical model provides mechanistic insights into the effectiveness of various radiotherapy schedules and guidelines for how modifying the tumor microenvironment to restore perfusion can affect radiation therapy.